Well-Defined Polyethylene Glycol Microscale Hydrogel Blocks Containing Gold Nanorods for Dual Photothermal and Chemotherapeutic Therapy - Ben Newland; Johannes Starke; Chiara Bastiancich; Diana P. N. Gonçalves; Laura J. Bray; Wenxin Wang; Carsten Werner (MDPI AG, 2022)
Local drug delivery offers a means of achieving a high concentration of therapeutic agents directly at the tumor site, whilst minimizing systemic toxicity. For heterogenous cancers such as glioblastoma, multimodal therapeutic approaches hold promise for better efficacy. Herein, we aimed to create a well-defined and reproducible drug delivery system that also incorporates gold nanorods for photothermal therapy. Solvent-assisted micromolding was used to create uniform sacrificial templates in which microscale hydrogels were formed with and without gold nanorods throughout their structure. The microscale hydrogels could be loaded with doxorubicin, releasing it over a period of one week, causing toxicity to glioma cells. Since these microscale hydrogels were designed for direct intratumoral injection, therefore bypassing the blood-brain barrier, the highly potent breast cancer therapeutic doxorubicin was repurposed for use in this study. By contrast, the unloaded hydrogels were well tolerated, without decreasing cell viability. Irradiation with near-infrared light caused heating of the hydrogels, showing that if concentrated at an injection site, these hydrogels maybe able to cause anticancer activity through two separate mechanisms.